THE METHOD EXAMINING COMPONENTS OF STUDENTS’ READINESS FOR SELF-EDUCATION - Martyniuk, Iryna (PSYCHOLOGICAL JOURNAL, 2020)
The article focuses on the importance of developing diagnostic tools for studying the structure of readiness of student youth for self-educational activities. The method of research of components of readiness for self-education activity of students is offered. The theoretical basis of the methodology is covered. The structure of readiness for self-educational activity is considered as a combination of personal, cognitive and activity components. Diagnosis of the personality component is carried out through questions aimed at identifying a positive attitude to the profession, understanding its requirements and their abilities (reflection), awareness of the importance of improvement, cognitive interest, sense of duty and responsibility, the ability to set goals and apply efforts to achieve it, to plan their activities. Diagnosis of the cognitive component is carried out through questions aimed at identifying the success of educational activities, awareness of educational activities as a direction of self-realization, the ability to work with sources of information, the ability to apply in practice the acquired special knowledge. Diagnosis of the activity component is carried out through questions aimed at identifying human understanding of the importance of self-education, the ability to penetrate into the essence of the problem (professional task), analyze possible solutions, set tasks and solve them, choose sources of knowledge, reflection of important skills of independent cognitive activity, desire and ability to plan their self-educational activities. The content of the method is given and the essence of the analysis of the results of the method is described. The reability and validity of the methodology are substantiated. It is noted that the proposed method of diagnosing the components of readiness of students for self-educational activities has good indicators of reliability and validity and can be used in the psychological practice of the educational process of universities.